Effect of training and recovery methods on vo2max athletes of unsika rowing club by controlling the effect of leg length - Deden Akbar Izzuddin Izzuddin; Nur Fitranto; Arrahman (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2022)
A well-executed training program using the right training method will result in an athlete's performance if the athlete gets sufficient recovery to recover from post-exercise fatigue. To find out the athlete's performance by knowing the oxygen volume capacity by using the balke test but the leg length of each athlete is suspected of contributing in carrying out the test so researchers want to examine the Effect of Training and Recovery Methods on VO2max of UNSIKA Rowing Club Athletes by Controlling the Effect of Leg Length. quasi-experimental method with a 2 x 2 factorial design. The research variables consisted of: (1) the dependent variable, namely VO2max Athlete Rowing Club UNSIKA (2) independent variables, namely the treatment variable (A1: Cross country method, and A2: Fatlek) and attribute variables ( B1: Passive Recovery and B2: Active Recovery) and (3) the covariate variable, in this study was Leg Length. So that the total number of research samples is 80 people. The Balke test is the test instrument used in collecting Vo2max data. as well as a tape measure to measure leg length. Hypothesis testing was carried out using two-way covariate analysis (ANKOVA) with a 2x2 factorial design. The results of the first hypothesis testing showed that the Vo2max results of the UNSIKA rowing club athletes between the athlete group using the cross country method were higher than the athlete group using the fatlek method after controlling for leg length. Thus the cross-country training method used in this study can improve the Vo2max results of UNSIKA rowing club athletes which are better than the fatlek method.